The Effect of Tax Amnesty, Understanding of Taxation, Tax Sanctions, and Tax Service Quality to Micro, Small, and Medium Enterprises Taxpayer Compliance During Covid-19 - Kenny Ardillah; Nabila Maharani Santoso (Universitas Padjadjaran, 2023)
This research aims to determine the effect of tax amnesty, understanding of taxation, tax sanctions, and service quality on Micro, Small, and Medium Enterprises' taxpayer compliance during COVID-19. The research population is Micro, Small, and Medium Enterprises taxpayers registered at Pratama Jakarta Pulo Gadung’s Tax Office. The sample of this research was determined using the Slovin method, with 99 respondents obtained. This research uses multiple regression analysis as a data analysis method. This research proves tax amnesty and service quality do not significantly influence Micro, Small, and Medium Enterprises' taxpayer compliance. Understanding taxation and tax sanctions positively affects Micro, Small, and Medium Enterprises' taxpayer compliance.